CARBONIC ANHYDRASE AS A MARKER OF OSTEOCLAST ACTIVITY IN THE REPAIR ZONE OF LONG BONE FRACTURE - I. A. Shurygina (Scientific Сentre for Family Health and Human Reproduction Problems, 2012)
In an experimental model of long bone fractures studied osteoclastic activity in the fracture zone. We used histological staining methods and histochemical staining with antibodies to carbonic anhydrase type II. It is shown that the use of histochemical staining to carbonic anhydrase type II cells is promising for the evaluation of osteoclastic activity in bone tissue. Application of this technique significantly simplifies the morphological study, allows a clear differentiation of osteoclastic cells.